(untitled) (Research, Society and Development, 2022)
The objectives of this study were to analyze and identify probable relationships between sedentary behavior and physical inactivity in children and adolescents, with the predominance of the Cartesian body concept in the school environment and the lack of learning about sports culture in Physical Education classes in elementary school. The research was based on a qualitative transversal approach with the participation of 19 students aged between 14 and 17 years, both sexes. The information collection instrument – questionnaire – discursive question submitted to the adapted technique of discourse analysis. It was identified that the devaluation of sports culture, which are apparently physical activities, in the school environment from the predominance of Cartesian conception of the body and the absence of access and appropriation of sports culture during Physical Education classes can contribute to sedentary behavior and inactivity. physical activity of children and adolescent students.